Bismuth Triflate Catalyzed Intermolecular Cyclization of Thiophenols with Allylic Alcohols - Minakawa, Maki; Inaba, Taichi; Oikawa, Shoki (Synlett, 2024)
The catalytic intermolecular cyclization of thiophenols with allylic alcohols in the presence of bismuth triflate afforded the corresponding thiochromane derivatives in a one-pot reaction. The Bi(OTf)3-catalyzed reaction was also applied to the intermolecular cyclization of diaryl disulfides with 3-methylbut-2-en-1-ol to produce the corresponding thiochromanes.
Keywords: S-heterocycles; bismuth catalysis; one-pot reaction; thiochromanes; thiophenols; allylic alcohols